Does intense monitoring matter? A quantile regression approach - Shawtari, Fekri Ali; Saiti, Buerhan; Mohamad, Muslim Har Sani; Abdul Rashid, Hafiz Majdi (Borsa Istanbul Anonim Sirketi, 2017)
Corporate governance has become a centre of attention in corporate management at both micro and macro levels due to adverse consequences and repercussion of insufficient accountability. In this study, we include the Malaysian stock market as sample to explore the impact of intense monitoring on the relationship between intellectual capital performance and market valuation. The objectives of the paper are threefold: i) to investigate whether intense monitoring affects the intellectual capital performance of listed companies; ii) to explore the impact of intense monitoring on firm value; iii) to examine the extent to which the directors serving more than two board committees affects the linkage between intellectual capital performance and firms’ value. We employ two approaches, namely, the Ordinary Least Square (OLS) and the quantile regression approach. The purpose of the latter is to estimate and generate inference about conditional quantile functions. This method is useful when the conditional distribution does not have a standard shape such as an asymmetric, fat-tailed, or truncated distribution. In terms of variables, the intellectual capital is measured using the value added intellectual coefficient (VAIC), while the market valuation is proxied by firm’s market capitalization. The findings of the quantile regression shows that some of the results do not coincide with the results of OLS. We found that intensity of monitoring does not influence the intellectual capital of all firms. It is also evident that intensity of monitoring does not influence the market valuation. However, to some extent, it moderates the relationship between intellectual capital performance and market valuation. This paper contributes to the existing literature as it presents new empirical evidences on the moderating effects of the intensity of monitoring of the board committees on the relationship between performance and intellectual.